Circularly Polarised Dielectric Resonator based Two Port Filtenna for Millimeter-Wave 5G Communication System. Issue 6 (2nd November 2022) - Kumar, Ashish; Dwivedi, Ajay Kumar; Nagesh, K. N.; Sharma, Anand; Ranjan, Pinku
Abstract : In this paper, a circularly polarised dielectric resonator-based MIMO filtering antenna is designed and analyzed. The unique feature of the proposed antenna is the combination of circular polarisation characteristics with filtering response at mm-wave. Cylindrical ceramic excited by asymmetrical plus-shaped slot provides two important characteristics: (a) generate dual orthogonal degenerated mode with 90 0 phase shifts in between 27.0 GHz and 27.33 GHz; and (b) produce the radiation nulls at 25.5 and 27.75 GHz respectively. Two identical ports are placed orthogonally to provide the lesser mutual coupling i.e . approx. −30 dB. Experimental outcomes confirm the operating band of the proposed antenna from 25.5 GHz to 27.79 GHz. In between the operating frequency range, the proposed radiator provides broadside radiation characteristics due to the creation of HE M 11 δ mode. The peak gain of the proposed antenna is about 5.0 dBi. Diversity parameters (such as ECC, DG, and TARC) are within satisfactory limits. All these properties of the proposed radiator make it fit for a 5G communication system.